THE ISSUES OF THE MODERN BUTLERIANA - Mukhiddinova (Abdullayeva) Dilafruz Mansurovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article presents Butler’s theory of evolution, where the main subject is Man. In addition, such random "variation" could not satisfy Butler, because he wants the world to be governed by laws, not by chance; and at the same time, he wants man to be the master of his own destiny. For Butler, evolution has a purpose, and that purpose is the desire of the being to change itself in accordance with the vital impulse. Butler’s theory of vitalistic evolution, based on mind and memory, is his most original contribution to biology.